Labour Admission Test - A low cost alternative to predict foetal distress and neonatal outcomes - Chandini Sree Lalitha Chinta; Sarvamangala B (Journal of Clinical and Biomedical Sciences)
Background and Objectives: The aim of various antepartum and intrapartum monitoring methods is to detect foetal hypoxia at the earliest and to prevent subsequent damage. Cardiotocography (CTG) is one of them. Routine and continuous EFM in labour is not possible in developing countries with limited resources and manpower. Objective of the study was to evaluate the role of CTG as admission test (AT) to predict foetal outcome in low and high-risk group. Methods: The study population consisted of 100 low risk and 100 high risk patients at term in labour admitted at WCH Hospital attached to J.J.M Medical College, Davangere. Patients were subjected to admission CTG for 20 minutes. The trace thus obtained was classified as normal, suspicious and pathological AT as per NICE 2017 Guidelines on Intrapartum Care. Results: Among the study group of 200 cases, including low and high-risk groups, 156 (95 & 61) cases had normal AT, 29 (5 & 24) cases had suspicious and 15 high risk cases had Pathological AT. The incidence of foetal distress, caesarean rate, Apgar score at 5 minutes less than 7, NICU admission was higher in pathological AT group than in normal AT. A statistical analysis comparing normal and abnormal (suspicious + pathological) AT showed high specificity 83.82% and high negative predictive value 92.95%. However, LAT was found to have low sensitivity 59.26% and low positive predictive value 36.36%. Conclusion: CTG as LAT is a simple, non-invasive, low cost test with high specificity and NP, that can be used to triage patients at the outset, thereby utilizing the limited equipment and staff effectively in resource poor labour wards. Keywords: Labour Admission Test, Cardiotocography, Perinatal Outcome, Electronic Fetal Monitoring